EVALUATION OF VO2MAX IN MORBIDLY OBESE PRE AND POST BARIATRIC SURGERY (Fiep Bulletin - online, 2014)
Introduction: Obesity is now a major public health problem, because the heavy weight, coupled with a sedentary lifestyle, is directly related to pathological conditions that cause high morbidity and mortality. Several interventions are used to improve health and therefore the quality of life of obese patients. The VO2max is a variable that should be assessed and monitored in the obese population, because it is an important parameter associated morbidities, and the quantification of the highest oxygen uptake by an individual is due to the interaction of the respiratory, cardiovascular and muscular. Objective: To evaluate the maximal oxygen uptake of morbidly obese individuals in the pre-and post-bariatric surgery. Methods: We evaluated 16 patients between 21 and 51 years, 3 patients were male and 13 female patients. These patients were already with the date of bariatric surgery marked, and returned to perform the test after 3 months of surgery. They signed an informed consent form and the project was approved by the IRB of the institution. Individuals performing treadmill exercise test following the protocol of Balke. Results: Statistical analysis revealed that the variables weight, stage and VO2max both pre and post-bariatric surgery had statistically significant. Conclusions: It was possible to identify that the obese population has compromised cardiorespiratory fitness, revealing values ??of maximum oxygen consumption lower when compared to the normal population, but after bariatric surgery VO2max values ??increased, which demonstrates an improvement in cardiorespiratory fitness.
Keywords: Obesity; VO2max; Bariatric Surgery.